SYNTHESIS AND SPECTROSCOPIC CHARACTERIZATION OF LITHIUM SALTS OF COPPER(II) AND NICKEL(II) COMPLEXES WITH 1,3-PROPANEDIAMINE-N,N,N’,N’-TETRAACETATE - Drašković, Nenad S; Gurešić, Dejan M (Bulletin of Natural Sciences Research, 2017)
The complexes Li2[Ni(1,3-pdta)]•5H2O and Li2[Cu(1,3-pdta)]•5H2O (where 1,3-pdta represents the 1,3-propanediaminetetraacetate anion) have been synthesized and characterized by applying IR and UV-vis spectroscopy. The obtained spectroscopic results of these complexes are discussed in relation to those for Mg[M(1,3-pdta)].8H2O complexes (M = Ni(II) and Cu(II)) of known crystal structure.